Review article: Has the implementation of time‐based targets for emergency department length of stay influenced the quality of care for patients? A systematic review of quantitative literature. (16th March 2021) - Jones, Peter; Haustead, Daniel; Walker, Katie; Honan, Bridget; Gangathimmaiah, Vinay; Mitchell, Robert; Bissett, Ian; Forero, Roberto; Martini, Ella; Mountain, David
Abstract: Time‐based targets (TBTs) for ED stays were introduced to improve quality of care but criticised as having harmful unintended consequences. The aim of the review was to determine whether implementation of TBTs influenced quality of care. Structured searches in medical databases were undertaken (2000–2019). Studies describing a state, regional or national TBTs that reported processes or outcomes of care related to the target were included. Harvest plots were used to summarise the evidence. Thirty‐three studies ( n = 34 million) were included. In some settings, reductions in mortality were seen in ED, in hospital and at 30 days, while in other settings mortality was unchanged. Mortality reductions were seen in the face of increasing age and acuity of presentations, when short‐stay admissions were excluded, and when pre‐target temporal trends were accounted for. ED crowding, time to assessment and admission times reduced. Fewer patients left prior to completing their care and fewer patients re‐presented to EDs. Short‐stay admissions and re‐admissions to wards within 30 days increased. There was conflicting evidence regarding hospital occupancy and ward medical emergency calls, while times to treatment for individual conditions did not change. The evidence for associations was mostly low certainty and confidence in the findings is accordingly low. Quality of care generally improved after targets were introduced and when compliance with targets was high. This depended on how targets were implemented at individual sites or within jurisdictions, with important implications for policy makers, health managers and clinicians. Abstract : Time‐based disposition targets for acute care have been in use for over 15 years, with no consensus about whether they should be retained. Thirty‐three studies from all jurisdictions using targets were included. Targets were associated with reduced mortality. There was improved access to care for admitted patients and fewer patients leaving prior to assessment. Despite evidence of a spike of admissions at the target threshold, more short‐stay admissions and higher re‐admission rates post‐hospital discharge, there was no evidence of systematic harm to patients. This review supports the retention of time‐based targets due to an overall benefit for patients that outweighs the potential harms